Nature, ethics, and gender in German Romanticism and idealism - Stone, Alison, 1972- (Rowman & Littlefield Publishers, 2018)
This book offers a unique account of the development of thinking about nature from Early German Romanticism into the philosophies of nature of Schelling, Hegel, and beyond. Alison Stone explores the ethical and political implications of German Romantic and Idealist ideas about nature, including for gender, race, and environmentalism.